MPSE identifies newborns for whole genome sequencing within 48 h of NICU admission - Bennet Peterson; Edwin F. Juarez; Barry Moore; Edgar Javier Hernandez; Erwin Frise; Jianrong Li; Yves Lussier; Martin Tristani-Firouzi; Martin G. Reese; Sabrina Malone Jenkins; Stephen F. Kingsmore; Matthew N. Bainbridge; et al. (npj Genomic Medicine)
Abstract Identifying critically ill newborns who will benefit from whole genome sequencing (WGS) is difficult and time-consuming due to complex eligibility criteria and evolving clinical features. The Mendelian Phenotype Search Engine (MPSE) automates the prioritization of neonatal intensive care unit (NICU) patients for WGS. Using clinical data from 2885 NICU patients, we evaluated the utility of different machine learning (ML) classifiers, clinical natural language processing (CNLP) tools, and types of Electronic Health Record (EHR) data to identify sick newborns with genetic diseases. Our results show that MPSE can identify children most likely to benefit from WGS within the first 48 h after NICU admission, a critical window for maximally impactful care. Moreover, MPSE provided stable, robust means to identify these children using many combinations of classifiers, CNLP tools, and input data types—meaning MPSE can be used by diverse health systems despite differences in EHR contents and IT support.